Adaptation Strategies of Coastal Communities to Sea Level Rise Due to Climate Change - Kamakaula, Yohanes (Westscience Press, 2024)
This study examines adaptation strategies employed by coastal communities in Indonesia to address sea level rise due to climate change. Utilizing a literature review method, the research identifies various adaptation strategies, their success factors, and the challenges faced by coastal communities. Findings reveal adaptation strategies including physical infrastructure development, mangrove rehabilitation, early warning systems, community education and awareness raising, livelihood diversification, resettlement, drainage infrastructure improvement, and sustainable coastal resource management. Each strategy presents its own strengths and challenges, necessitating a holistic and participatory approach for effective implementation. Recommendations include enhancing stakeholder collaboration, developing flexible policies responsive to local conditions, and increasing investments in education and infrastructure. Regular evaluation of adaptation strategy success is also advised to ensure sustainability of adaptation efforts in the future.